Torsion (Torsion Free) Fuzzy Modules Over Fuzzy Integral Domain - Hadi, I. M. A.; Hamil, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study of torsion torsion free) fuzzy modules over fuzzy integtal domain as a generalization oftorsion (torsion free) modules.